(untitled) (Education in the 21st Century, 2023)
The article deals with the system of quality management of professional training of specialists in accordance with the legal framework. It has been determined that the main components in quality assurance of education in Ukraine are the systems of quality assurance in the institutions of professional education; the system of external quality assurance of education; the quality assurance system in the activities of management bodies. The concept of "quality management system" is justified as a set of interrelated or interdependent elements that enable to establish the policy and goals and ways of achieving these goals and are directed to control the activities of the quality institution. The directions (strategies) of development of the quality management system, which are aimed at improving the efficiency and effectiveness of the activity of the institution of professional education and carrying out the appropriate certification (accreditation, licensing) and obtaining the quality certificate, have been established. The influence of target functions of quality management of vocational (vocational-technical) education on the content and structure of managerial functions of the head of the institution of vocational education in terms of integrative learning has been determined. The content of technological managerial functions of the head of the institution of professional education in the conditions of integrative learning and innovative methods of management of quality of professional training of specialists is revealed. The experience of the European Union countries in the direction of achieving efficiency and effectiveness in managing the quality of professional training of specialists has been researched. The concept of benchmarking, controlling, monitoring, fundraising as components of the management system contributing to the ordering and regulation of the activity of vocational education institutions is revealed; a clearer distribution of powers, tasks and responsibilities through prescribing and managing processes; improving the quality of the provision of educational services, awareness of it and taking into account the needs and expectations of consumers; rational and efficient use of resources, especially human resources; increased prospects for contacts with potential investors.